PEMANFAATAN LIMBAH PERTANIAN & TERNAK SEBAGAI BAHAN PUPUK ORGANIK UNTUK USAHA PERTANIAN - Teguh Wijayanto; La Ode Arfan Dedu; Anima Hisein (Universitas Halu Oleo, 2023)
The manufacture and application of compost fertilizer and POP technology (organic fertilizer plus) was carried out in the community in Alebo Village and/or Masagena, Konda District, South Konawe Regency, both for non-productive communities and owners of livestock waste processing. Alebo and Masagena villages are vegetable and annual crop farming areas, which are cultivated throughout the year and generally depend heavily on chemical fertilizers. Therefore, POP and/or compost technology is needed to improve the quality of soil nutrients and increase the production of healthy plants. In the villages of Alebo and Masagena there are abundant reservoirs for livestock waste and rice husks but they have not been processed optimally, but are only sold in the form of rice husks and raw cow husks at relatively cheap prices so that they do not provide added value for the village community, so this community service activity was done to improve environmental conditions which had been polluted due to the use of chemical fertilizers, and can also increase the income of local communities by utilizing existing waste to make organic fertilizer (compost and POP). Organic fertilizer has a higher price than livestock waste and unprocessed rice husks. The solution implemented in this service activity was the application of technology to change the use of chemical fertilizers by using POP technology and compost fertilizer so that farming land is even more productive.